Pride and the city - Morrison, Philip S (REGION, 2016)
Pride in one’s city is an individual, and collective as well as institutional response to urban conditions which may be harnessed in support of expanding urban facilities and services. Pride is likely to be felt most keenly by those who have a stake in the city and for this reason anecdotal reporting of urban pride in the media is subject to likely bias in favour of vested interests. In practice however we know very little about urban pride. The vast literature on urbanism does not appear to have identified any role for urban pride let alone indicating which cities gather pride or who among its inhabitants exhibit such pride This paper applies a multi-level statistical model to large random sample of residents in twelve New Zealand cities. From the results we learn that, although financial stake holding is relevant, urban pride is concentrated more broadly among those whose social and cultural identity is closely tied to the city. Where financial stake holding is most influential is when it is absent, for those experiencing financial difficulties are the most likely to disavow urban pride. Urban pride is a therefore a distributional property of cities in which the currencies are emotional and cultural as well as financial. Urban pride is relatively absent among those who fail to have a stake in the city as well as being weaker among those who live in relatively unattractive cities, and less attractive neighbourhoods. As a barometer of rewards to living and investing in the city, urban pride certainly warrants closer attention than it has received to date.